Effect of Position of Fruits in a Tree and Number of Fruits per Panicle on Growth and Quality of Citrus - Sakhidin; Teixeira da Silva Jaime A.; Suparto Slamet Rohadi (Journal of Horticultural Research, 2018)
This research aimed to study the effect of the position of fruits in a tree (inner or outer) and the number of fruits per panicle (one, two or three) on the growth and quality of citrus ‘Pontianak’. The study was conducted in a citrus orchard in Central Java, Indonesia for two seasons, 2014/2015 and 2015/2016. The results indicated that position of fruits on the tree did not influence weight and diameter of fruits, weight of fruit pulp, and contents of sugars and total acids. Increasing the number of fruits per panicle decreased the weight and diameter of fruits and the weight of pulp but increased the contents of vitamin C and total acids.